2018
DOI: 10.1080/13501763.2017.1401112
|View full text |Cite
|
Sign up to set email alerts
|

Pro-elderly welfare states within child-oriented societies

Abstract: Households and policies are the main vehicles of intergenerational transfers. Working-age people are net contributors; children and older persons net beneficiaries. However, there is an asymmetry in socialization. Working-age people pay taxes and social security contributions to institutionalize care for older persons as a generation, but invest private resources to raise their own children, often with large social returns. This results in asymmetric statistical visibility. Elderly transfers are near-fully obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…This result is in line with the analysis of Bruno, Marelli, and Signorelli (2015) who found that both NEETs and unemployment rates respond slowly to an increase in GDP, with many years elapsing before the situation of the young improves. In addition, as recent studies on intrafamilial transfers suggest (Gál, Vanhuysse, andVargha 2018, Francesconi andHeckman 2016), there is a danger in looking at data on public transfer alone without considering intergenerational transfers (cash) and the household economy (time), as social investments may have a differential impact across childhood and early youth through family investments.…”
Section: B Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in line with the analysis of Bruno, Marelli, and Signorelli (2015) who found that both NEETs and unemployment rates respond slowly to an increase in GDP, with many years elapsing before the situation of the young improves. In addition, as recent studies on intrafamilial transfers suggest (Gál, Vanhuysse, andVargha 2018, Francesconi andHeckman 2016), there is a danger in looking at data on public transfer alone without considering intergenerational transfers (cash) and the household economy (time), as social investments may have a differential impact across childhood and early youth through family investments.…”
Section: B Resultsmentioning
confidence: 99%
“…Moreover, in line with the analysis of Bruno, Marelli, and Signorelli (2015), our results suggest that youth labor market indicators are less responsive to variation in compensatory spending as the total effects of a shock in these policy variables do not ultimately lead to an increased participation of the youth in the labor market. These results also highlight the importance of explicitly considering the role of intrafamilial transfers in future analysis as social investments may have a differential impact across childhood and early youth through family investments (Gál, Vanhuysse, andVargha 2018, Francesconi andHeckman 2016). At the same time, we need to be cautious as we did not consider any redistributive/differential effect that such policies can have at the individual levels (Bonoli and Liechti 2018;Pavolini and Van Lancker 2018), nor any regional spillover effects that policies can have among regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Transfer Accounts (NTA) project, designed to trace both private and public intergenerational transfers, acknowledges the value of unpaid care work, which have been added to NTA accounts for several countries (Iván et al 2018;Donehower 2019). In the U.S., public transfers to the elderly through Social Security and Medicare are counterbalanced by extensive family expenditures on the younger generation (Lee et al 2017).…”
Section: How Best To Value Non-market Expenditures and Transfers?mentioning
confidence: 99%
“…For example, age structure and life course flows of resources are important for discussions of sustainability of pension systems in contemporary societies, as well as the value of having more children in low fertility societies 1(e.g. Cigno & Werding, 2007;Gál, Vanhuysse, & Vargha, 2018).…”
Section: Implications Of Demographic Theory For Population Ethicsmentioning
confidence: 99%